Estimated glomerular filtration rate and the risk–benefit profile of intensive blood pressure control amongst nondiabetic patients: a post hoc analysis of a randomized clinical trial. (19th November 2017) - Obi, Y.; Kalantar‐Zadeh, K.; Shintani, A.; Kovesdy, C. P.; Hamano, T.
Abstract: Background: The Systolic Blood Pressure Intervention Trial (SPRINT;ClinicalTrials.gov, NCT01206062) reported reduced cardiovascular events by intensive blood pressure (BP) control amongst hypertensive patients without diabetes. However, the risk–benefit profile of intensive BP control may differ across estimated glomerular filtration rate (eGFR) levels. Methods: This is a post hoc analysis of the SPRINT. Nondiabetic hypertensive adults ( n  = 9361) with eGFR >20 mL per min per 1.73 m 2 were enrolled from 102 US facilities between November 2010 and March 2013 and were followed up until August 2015 (median follow‐up, 3.26 years). Patients were randomly assigned to either a systolic BP target of <120 or <140 mmHg (for intensive or standard treatment, respectively). The outcomes of interests were the development of (i) fatal and nonfatal major cardiovascular events and (ii) acute kidney injury (AKI). Results: The cardiovascular benefit from intensive treatment was attenuated with lower eGFR ( P interaction  = 0.019), whereas eGFR did not modify the adverse effect on AKI ( P interaction  = 0.179). Amongst 891 participants with eGFR <45 mL per min per 1.73 m 2, intensive treatment did not reduce the cardiovascular outcome (54/446 vs. 54/445 events in the standard group, respectively; hazard ratio [HR], 0.92; 95% CI, 0.62–1.38) with an absolute rate difference (ARD) of −0.02 (95% CI, −0.07 to +0.03) per 100 patient‐years, whereas it increased AKI (62/446 vs. 38/445 events in the standard group; HR, 1.73; 95% CI, 1.12–2.66) with an ARD of +1.93 (95% CI, +1.88 to +1.97) per 100 patient‐years. Conclusions: Intensive BP control may provide little or no benefit and even be harmful for patients with moderate‐to‐advanced chronic kidney disease. Abstract : Click here to view the Editorial Comment by F. H. Messerli et al.